Faktor-faktor Penentu Perilaku Mencontek di Kalangan Mahasiswa Fakultas Ekonomi UNP - Friyatmi, Friyatmi (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT Cheating on test, which is a perennial problem in higher education, is a fraudulent act that could result a blurred evaluation process. This study aims to identify the characteristics of cheating behaviour on test and to analyze determining factors of cheating behaviour among students of Economic Faculty, the State University of Padang. This study was an ex-post facto. The data in this study were collected through quetionnaire and analyzed with descriptive and factor analysis techniques. The results of this study indicated that there are some characteristics of studentâ€™s cheatingÂ behaviour: 39,7% of them used materials or aids that have not been approved by lecturer, 62,7% copied the answers from their friends or allowed the answers to be copied, 58,8% shared the answers or consulted them with their friends, and 27,8% accessed the answers outside the room. The determining factors of cheating behaviour consisted of: mastery of the material, learning factors, success story, self-concept, personal motives, situational, and social factors. Kata Kunci: Perilaku, mencontek, ujian (test)